MAKING OPTIMAL DECISIONS BY CONSUMERS IN THE MARKET IN THE CONTEXT OF DIGITAL MARKETING DEVELOPMENT - Aliyeva, Gunay; Adigozelova, Havva; Nabiyev, Aydin; İsmayılov, Vilayat and Mammadova, Firana (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The purpose of this work is to study the influence of digital marketing channels on consumer purchasing decisions. The first part included demographic issues . The second part included the impact of the use of the Internet and digital marketing channels on the purchase of goods, in order to determine the impact of these channels on consumer decision-making. Of the 290 respondents who use the Internet daily, more than 63% said they are connected to social media and marketing emails. 93 participants expressed their opinion about websites that have a greater impact on consumer decision-making. 190 participants also stated that they often buy products using digital marketing channels.The scientific novelty of the study is that consumer decision-making in the digital economy is characterized by reduced information costs, high speed of comparing prices and goods, as well as the use of big data and AI recommendations. The consumer gets access to a wide range of choices, but is faced with manipulative strategies of companies such as "obfuscation". At the same time, factors such as access to information, the role of platforms and data, optimization and manipulation, network effects, etc. are considered key aspects of the decision-making process in the digital age. Therefore, professionals should carefully study their target audience and act in accordance with consumer behavior in order to gain a competitive advantage when placing their products or services on websites and social media accounts. From a practical point of view, the research results can be useful to marketers and specialists working in this field. The research also specifies the principles of consumer choice when making optimal decisions. In addition, it helps customers determine which approach to digital marketing strategy is needed. This approach allows companies to develop their digital strategies with more precise targeting.